Harnessing Technology for Educational Assessment: An In-Depth Analysis of Quizizz in Economics Classrooms - Suranto; Niswatul Mafariha; Djalal Fuadi (Jurnal VARIDIKA, 2024)
Technological advancements in classroom education are evolving at a rapid pace, offering a multitude of innovative applications, particularly for assessment purposes. This study offers a comprehensive analysis of the strengths, benefits, and limitations of the Quizizz assessment application within the context of high school economics education. Adopting a qualitative research methodology with a case study design, the study collects data through interviews, observations, and documentation. The participants in this research include economics teachers and 8th-grade and 11th-grade social science students from a private school in Indonesia who have utilized Quizizz for their economics classes. To ensure the validity of the data, both source and technique triangulation are employed. The data analysis process involves three main steps: data reduction, data presentation, and conclusion drawing. The findings reveal that the Quizizz application significantly enhances student motivation and engagement in the learning process. The benefits of Quizizz include creating an enjoyable learning environment and fostering a competitive spirit among students. However, the study also identifies some challenges, such as issues with internet connectivity and the potential for academic dishonesty, which have been addressed through various measures.